In Search of a Perfect Form and Style: Turgenev andConrad’s Emphasis on Visual Impression - Pudełko, Brygida (Poznańskie Studia Slawistyczne, 2013)
The human face as a mask that can both hide and emphasise the main traits of human personality and thoughts was used by Turgenev and Conrad. In the society depicted in such novels as Under Western Eyes, Virgin Soil and Smoke where secrecy and hypocrisy are a universal condition of man, face reading becomes an essential factor. The references to eyes as well as words and outside look indicate something about the characters concerned and can be considered as a means attributing a moral significance to physical appearance. As eyes are closely related to communication and knowledge, comments about the characters’ eyes implicate their knowledge and honesty with which they communicate with other people.